(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Belt and Road Initiative proposed by China and development strategy it involves set a goal to build connectivity and cooperation across six main economic corridors encompassing China and: [Mongolia and Russia; Eurasian countries; Central and West Asia; Pakistan; countries of the Indian sub-continent; and Indochina. Currently, Asia needs 23 trillion in infrastructure investment by 2025 (Asian Development Bank, 2017), and China can definitely help to provide some of this sum. Its investments in constructing infrastructure are having positive impacts on the countries involved. Mutual benefit is a feature of the BRI which will also help to develop markets for China’s products in the long term and to increase industrial excess capacity in the short term. This report explores and quantifies parts of the BRI strategy, the impact on other BRI-participating economies, and some of the implications for Uzbekistan.